The liberation of the camps : the end of the Holocaust and its aftermath - Stone, Dan 1971- (Yale University Press, 2015)
Introduction: explaining liberation -- Liberated by the Soviets -- The Western allies -- Out of the chaos -- Displaced persons (dps) or betrayed persons (bps)? life in the dp camps -- Transitions: dps in a changing world -- Conclusion: the sorrows of liberation